Effects of modified lipoproteins on human trophoblast cells: a role in pre-eclampsia in pregnancies complicated by diabetes - Rebecca Helen McLeese; Jiawu Zhao; Dongxu Fu; Jeremy Y Yu; Derek P Brazil; Timothy J Lyons (BMJ Open Diabetes Research & Care, 2021)
Introduction Pre-eclampsia (PE) is increased ~4-fold by maternal diabetes. Elevated plasma antiangiogenic factors, soluble fms-like tyrosine kinase (sFLT-1) and soluble endoglin (sENG), precede PE onset. We investigated whether diabetes-related stresses, modified lipoproteins and elevated glucose enhance trophoblast sFLT-1 and sENG release and/or alter placental barrier function and whether oxidized low-density lipoprotein (Ox-LDL) is in placental tissue.Research design and methods HTR8/SVneo cells were exposed to ‘heavily-oxidized, glycated’ LDL (HOG-LDL) versus native LDL (N-LDL) (10–200 mg protein/L) for 24 hours ±pretreatment with glucose (30 mmol/L, 72 hours). Concentrations of sFLT-1 and sENG in supernatants (by ELISA) and expressions of sFLT-1-I13 and sFLT-1-E15A isoforms, endoglin (ENG) and matrix metalloproteinase-14 (MMP-14; by RT-PCR) were quantified. For barrier studies, JAR cells were cultured in Transwell plates (12–14 days), then exposed to LDL. Transepithelial electrical resistance (TEER) was measured after 6, 12 and 24 hours. In placental sections from women with and without type 1 diabetes, immunostaining of apolipoprotein B100 (ApoB, a marker of LDL), Ox-LDL and lipoxidation product 4-hydroxynonenal was performed.Results HOG-LDL (50 mg/L) increased sFLT-1 (2.7-fold, p<0.01) and sENG (6.4-fold, p<0.001) in supernatants versus N-LDL. HOG-LDL increased expression of sFLT-1-I13 (twofold, p<0.05), sFLT-1-E15A (1.9-fold, p<0.05), ENG (1.6-fold, p<0.01) and MMP-14 (1.8-fold, p<0.05) versus N-LDL. High glucose did not by itself alter sFLT-1 or sENG concentrations, but potentiated effects of HOG-LDL on sFLT-1 by 1.5-fold (p<0.05) and on sENG by 1.8-fold (p<0.01). HOG-LDL (200 mg/L) induced trophoblast barrier impairment, decreasing TEER at 6 hours (p<0.01), 12 hours (p<0.01) and 24 hours (p<0.05) versus N-LDL. Immunostaining of term placental samples from women both with and without diabetes revealed presence of intravillous modified lipoproteins.Conclusion These findings may explain, in part, the high risk for PE in women with diabetes. The trophoblast culture model has potential for evaluating novel therapies targeting barrier dysfunction.